Correction: Corrigendum: Potent single-domain antibodies that arrest respiratory syncytial virus fusion protein in its prefusion state - Iebe Rossey (Nature Portfolio, 2017)
Nature Communications 8: Article number: 14158 (2017); Published 13 February 2017; Updated 29 November 2017. In this Article, the clinical isolate MAD/GM3_10/14 of respiratory syncytial virus (RSV) is incorrectly described as an RSV A isolate. MAD/GM3_10/14 has been identified as an RSV B isolate onthe basis of its fusion protein sequence.